Acesso da pessoa com deficiência ao ensino médio público estadual em Sergipe - Silva, Antonella Moura da (2023)
This dissertation dealt with the access of people with disabilities to state public high school in Sergipe. Its general objective was to map the access of people with disabilities to state public secondary education in Sergipe and the specific objectives were: to investigate aspects of special education in Sergipe; specify the sociodemographic elements of the disabled population enrolled in state public high school in Sergipe (gender and race/color); to identify the predominance of types of disability in relation to the number of student enrollments in state public high schools in Sergipe. To achieve these objectives, the study was developed with a quantitative and qualitative approach to measure and understand the aspects that characterize the access of people with disabilities to state public secondary education in Sergipe. It was a descriptive research. The study had enrollments of people with disabilities in the state public network in Sergipe as a research universe and, as a sample, enrollments in high school. The time frame of the research was from 2016 to 2020. As the year 2016 was the period in which Law No. of Decree No. 10502 which institutes the National Policy on Special Education with the proposal of an inclusive, equitable education with lifelong learning. For the collection of information, data provided by the National Disability Information System - SISDEF were used. When considering the results found with the development of the research, it is considered that the access of people with disabilities to state public high school in Sergipe is still restricted, considering the total population with disabilities residing in the State and the number of enrollments analyzed , although there has been some progress in relation to the actions of state power to expand this population's access to the state educational system.